Pengaruh Pemberian Jenis Pupuk terhadap Pertumbuhan Vegetatif Tanaman Jagung (Zea mays L.) Hibrida - Yulianto, Rahmat Dwi (Program Studi Agroteknologi, 2025)
One of the main commodities that Indonesia strategically uses to support its economy and growth is maize. This commodity is promising as a food alternative to rice, which is a valuable commodity with a high market value and is often used as the main raw material for animal feed. Plants that lack N, P, and K will experience nutrient deficits in corn plants, resulting in suboptimal growth characterized by stunting and even death. When the needs of N, P, and K are met, plants will develop optimally. The research was conducted from December 2022 to January 2023 in the Greenhouse of Seed Production Engineering of Jember State Polytechnic, this research used a non-factorial Randomized Group Design (RGD) design with one factor repeated 3 times. If there is a significant difference between treatments, further test will be conducted using DMRT (Duncan Multiple Range Test). The results showed that the treatment of N, P and K fertilizer deficiency did not experience a significant effect or not significantly different from the vegetative growth of age (30 DAP) in hybrid corn plants.